1989
DOI: 10.1161/01.cir.79.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Trends for coronary heart disease and stroke and their risk factors in Japan.

Abstract: Disease surveillance and population surveys of risk characteristics in a northeast rural community of Japan (1965 census population, 7,030) are combined in an attempt to relate morbidity and risk factor trends for coronary heart disease and stroke during the last 2 decades. Between 1964 and 1983, the incidence of coronary heart disease (i.e., combined myocardial infarction, angina pectoris, and sudden death) did not change significantly among men and women ages 40-69, and was lower than that for stroke. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
217
5

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(230 citation statements)
references
References 24 publications
5
217
5
Order By: Relevance
“…The fact that a greater proportion of the ischaemic stroke cases were lacunar strokes (64%) rather than large-artery occlusive infarctions suggests that this may be the case. In hypertensive subjects, glucose abnormalities may not play a prominent role in the pathogenesis of stroke because hypertension is the predominant risk factor for stroke [3,7]. Alternatively, it is possible that this finding was due to chance alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that a greater proportion of the ischaemic stroke cases were lacunar strokes (64%) rather than large-artery occlusive infarctions suggests that this may be the case. In hypertensive subjects, glucose abnormalities may not play a prominent role in the pathogenesis of stroke because hypertension is the predominant risk factor for stroke [3,7]. Alternatively, it is possible that this finding was due to chance alone.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were followed-up to identify the number of incident strokes that occurred up to the end of 2000. The details of endpoint determination have been previously described elsewhere [7]. Briefly, to obtain histories of incident strokes, participants completed annual cardiovascular risk surveys.…”
Section: Methodsmentioning
confidence: 99%
“…35 The major type of stroke in Taiwan is cerebral infarction while for Japan and China, it is cerebral haemorrhage. 36,37 In Japan twice as many men (2.1) and women (2.6) die from stroke as from CAD. Chonghna et al 38 found that the incidence of stroke is four times that of acute myocardial infarction in some areas of China.…”
Section: Burden Of Cardiovascular Disease In Asiamentioning
confidence: 99%
“…[36][37][38][39] A strikingly similar situation prevailed in Japan before the 1960s, when there was high dietary salt intake and low animal protein and fat intake, with strenuous labour-intensive work and poor housing conditions. 40 All these factors may have contributed to the high blood pressure levels, especially SBP level, in that period in the Japanese population. The INTERSALT study also suggested that a higher SBP level in Japanese than in US white population may be attributable to a higher sodium intake for men and women and to a higher alcohol intake for men in Japan.…”
Section: Major Risk Factors Of Hypertensionmentioning
confidence: 99%